The Phylosophy of Religion in Abraham Joshua Heschel:: The lack of Self-discernment and the Eclipse of God in Modernity - Guerra, Danilo Dourado (2021)
In this text, in an attempt to understand the methodological concept of self-discernment found in the philosophy proposed by Abraham Joshua Heschel, we aim to pay attention to his understanding of the concept of “Man,” since self-discernment presupposes the man who seeks his transcendental essence. Moreover, for Heschel philosophy has the function of analyzing religion as responsible for man’s fundamental answers when religion fails to do so, either it has become ineffective or modern man has become animalized, indiscernitant. The phenomenon of God’s Eclipse in modernity is therefore structured. To inventory such philosophical nuances in the light of Abraham Joshua Heschel becomes the challenge we propose in the sequential path of this article.